IN SILICO IDENTIFICATION AND CHARACTERIZATION OF MUTUAL EPITOPE-BASED SUBUNIT VACCINE AGAINST EBOLA VIRUS AND MARBURG VIRUS - SHARMA, SAMEER; JADHAV, SUPRIYA; YADAV, POOJA (Innovare Journal of Life Sciences, 2020)
Objective: The objective of the study was to analyze the mutual epitope-based vaccine that can evoke immune response against hemorrhagic fever caused by Ebola virus (EBOV) and Marburg virus (MARV). Methodology: VP40, VP24, VP35, VP30, and NP proteins of Ebola and MARV were recovered from the protein database and subjected to many bioinformatics tools to predict the best B- and T-cell epitopes. And finally, the selected proteins were subjected to molecular docking human leukocyte antigen (HLA)-DR (major histocompatibility complex [MHC] Class I and II) to confirm their antigenicity in silico. Results: The epitopes from EBOV were stable while were unstable from MARV. Further, molecular docking simulation using most significant MHC Class II and Class I molecules demonstrated that their epitopes may bind within HLA-binding affinity to evoke an immune response. Conclusions: In this study, the data revealed the epitopes from VP40 protein could be the specific target for peptide-based vaccine design against Ebola and MARV.